The effect of job design on job satisfaction levels among employees in Syarikat Air Johor (SAJ) Holdings Sdn. Bhd. Kota Tinggi / Latifah Abdul Hamid and Nur Syahirah Salwey - Abdul Hamid, Latifah; Salwey, Nur Syahirah (Faculty of Business and Management, 2016)
There is a need to determine if the way a job is designed has an impact on employee‟s satisfaction level. This study examines the effect of job design on job satisfaction among employees in selected organization. The study covered a sample of 136 respondents drawn from a total population of 214 employees in SAJ Holdings Sdn. Bhd. Kota Tinggi. The sample was selected through simple random sampling techniques. Primary data was collected through the use of questionnaires. A pilot study was undertaken on 20 employees to test the reliability and validity of the questionnaire. Data analysis that have been used in this research study are Pearson Correlation analysis, and Multiple Regression analysis. From the findings of Pearson Correlation analysis, all independent variables (job rotation, job enlargement, and job enrichment) are significantly related to job satisfaction. In addition, job rotation is the most variable that related to job satisfaction. Finally, the most important independent variable in the regression model was job rotation as it had the highest Beta value of 0.902. The study found out that job design affects job satisfaction levels among employees in SAJ Holdings Sdn Bhd. where both independent and dependent variables move in the same direction. It indicates that proper job design brings more job satisfaction and vice versa for the employees.